Verification of phosphorus critical level for bread wheat (Triticum aestivum L.) in Kofole District of West Arsi Zone, Oromia, Ethiopia - Husien, Abdurahman; Firomsa, Tilahun; Abera, Tilahun (Food Biology, 2021)
Verification of phosphorus critical level for bread wheat was conducted in Kofole District in 2019 cropping season with the objectives to verify phosphorus critical (Pc) level and determined during soil test crop response based phosphorus fertilizer calibration and to create awareness on soil test crop response based fertilizer recommendation. Composite soil samples at the depth of 0-20 cm in the zigzag method were collected from 10 farmers’ fields for Eutric Vertisols. Likewise, soil samples analyses were made to identify available P in the level of the required phosphorus in the select crop fields for the actual experiment. The treatments included (1) soil test based phosphorus calibration result; (2) farmers’ practice in the area which was assessed by the surrounding farmers’ and (3) no fertilizer application (control) and each treatment was planted on 10*10m experimental plot & the design was randomized complete block design replicated over farmers. Bread wheat, Ogolcho variety, was used with seed rate of 150 kg ha-1and other cultural practices such as weed and rust management were used from which had been recommended for the area. The partial budget analysis showed that the highest net income (71630.48 ETB) was from the soil test based recommended and the lowest net benefit (44378.55 Birr ha-1) was obtained from control treatment with a marginal rate of return (653.38%) which is greater than the minimum rate of return (MRR) 100%. The result showed that the average grain yield of 4745 kg ha-1 was obtained from the application of soil test based phosphorus calibration (Pc and Pf) followed by blanket recommendation (3853 kg ha-1) and 2778 kg ha-1 for the control treatment. The recommended N rate, 69 kg N ha-1 with soil test based phosphorus critical level gave a 58.54% grain yield advantage over the control. In general, soil test and crop response based fertilizer recommendation for crops increases crop yields through the application of adequate nutrient rates for the identified soil nutrient deficiencies in specific locations.